2007
DOI: 10.1002/chem.200700649
|View full text |Cite
|
Sign up to set email alerts
|

Structural Importance of Secondary Interactions in Molecules: Origin of Unconventional Conformations of Phosphine-Borane Adducts

Abstract: The series of phosphine-borane adducts, Ph2(H3C--C[triple chemical bond]C)P--B(C6F5)3 (8 c), Ph(H3C--C[triple chemical bond]C)2P--B(C6F5)3 (8 b) and (H3C--C[triple chemical bond]C)3P--B(C6F5)3 (8 a), was prepared. The X-ray crystal structure analyses revealed close to eclipsed conformations for all members of this series with average dihedral angles theta(C-P-B-C) of 8.1 degrees (8 c), 12.3 degrees (8 b) and 20.3 degrees (8 a). Quantum chemical analysis of these compounds revealed the importance of a subtle in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 86 publications
0
49
0
1
Order By: Relevance
“…The B-P distance in (F 5 C 6 ) 3 B-PPh 3 is 2.180(6) Å; 5 we predict 2.158 Å, an improvement over the DFT-D-PBE/ TZVP level prediction of 2.22 Å. 6 With this in mind, we note the method predicts a B-P distance of 3.838 Å for (F 5 C 6 ) 3 BP(t-Bu) 3 , some 0.4 Å shorter than that predicted by Pàpai et al 3 Second, the M-P bond distances in the (F 5 C 6 ) 3 B-PR 3 series are nearly identical for R ) Me and Et, increase about 0.1 Å for R ) i-Pr and Ph, and then increase again for R ) t-Bu (substantially for M ) B). This suggests similar steric bulk for i-Pr and Ph substituents, somewhat at odds with their suggested cone angles.…”
Section: Resultsmentioning
confidence: 95%
“…The B-P distance in (F 5 C 6 ) 3 B-PPh 3 is 2.180(6) Å; 5 we predict 2.158 Å, an improvement over the DFT-D-PBE/ TZVP level prediction of 2.22 Å. 6 With this in mind, we note the method predicts a B-P distance of 3.838 Å for (F 5 C 6 ) 3 BP(t-Bu) 3 , some 0.4 Å shorter than that predicted by Pàpai et al 3 Second, the M-P bond distances in the (F 5 C 6 ) 3 B-PR 3 series are nearly identical for R ) Me and Et, increase about 0.1 Å for R ) i-Pr and Ph, and then increase again for R ) t-Bu (substantially for M ) B). This suggests similar steric bulk for i-Pr and Ph substituents, somewhat at odds with their suggested cone angles.…”
Section: Resultsmentioning
confidence: 95%
“…This implies that the repulsive secondary interaction is more important than the attractive one in this case between these side chains, and suggests that the perfluorophenyl to tertbutyl interaction is not the main governing factor for the characters of the pair. This is in contrast to other phosphine-borane adducts reported by Spies et al with high content of aromatic substitutions, [44] and can be rationalized based on the drastic difference between aromatic-aromatic and aromatic-alkyl dispersion interactions.…”
mentioning
confidence: 71%
“…These species formed strong intramolecular phosphorus/boron Lewis acid/base adducts. [16,17,18] Studies of the conformational properties revealed heteroalkane-like behavior.…”
Section: Heterolytic Activation Of H 2 By Phosphine/boranementioning
confidence: 99%